The aftermath of the EU-Turkey deal - Langi, Angela Martina (Riga Graduate School of Law, 2022)
The deal between the EU and Turkey was one of the responses to the migration problem in Europe. The Statement's ambiguous legal status generated debates on EU law compliance. This work intends to address the latter issue especially by focusing on a EU General court’s ruling concerning migration-related rights and the EU-Turkey Statement. The dismissal of the case involving several plaintiffs affected by the deal was rooted on the authorship of the Statement. The General Court concluded that the Statement cannot be regarded as an act of the European Council or any other EU institution. This study attempts to assess the legal nature of the EU-Turkey Statement in order to contextualise the decisions of the General Court. To analyse the legal nature of the EU-Turkey Declaration, two separate questions will be addressed: the legal nature of the Statement as an international agreement or the legal nature of the Statement as a political statement of the European Council meeting with Turkey. Following that, the remainder of this research examines how the agreement has impacted the European migrant crisis and what the major issues are.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; EU-Turkey Statement; The European Union; Migration; The Republic of Turkey